Solid-liquid extraction of hydrolysable tannin (galic acid) from stem bark of Jatropha Curcas using various type of extraction - Amirah, Izam (2012)
Extraction and product recovery are the most crucial steps in evaluation of valuable active compounds from various plant parts.In this study,extraction of gallic acid from Jatropha curcas stem bark was investigated.The aims of this study were to study the extraction parameters using four different extraction techniques,to estimate the kinetic studies of gallic acid,to optimize the ultrasonic-assisted extraction(UAE)parameters and to compare the efficiency of extraction techniques.Two conventional extraction techniques were employed such as shake flask extraction and Soxhlet extraction.Ultrasonic-assisted extraction(UAE)and microwave-assisted extraction(MAE)were the modern extraction techniques utilized.The effect of solvent composition, extraction time,extraction temperature and power for UAE and MAE were the extraction parameters used in the extraction studies.For the shake flask extraction and Soxhlet extraction,two parameters namely as effect of solvent composition and extraction time were evaluated.The extracts were further undergone analysis process.Quantification of gallic acid in the extracts was done using high-performance liquid chromatography(HPLC).In general,all the extraction techniques were capable of isolating gallic acid from the bark,but the recovery obtained using modern techniques was higher than the conventional techniques.It was found that all the parameters studied had given significant effect towards the yield of gallic acid.Kinetic studies were done to estimate the washing coefficient and the slow extraction coefficient.Washing of extractive substances from the surface of plant particles phenomena is happening before it reaches equilibrium and then slow extraction process is happening until it reaches equilibrium.In optimization part, the parameters of UAE(solvent composition,extraction temperature and extraction time) were optimized using Box-Behnken Design(BBD).The optimal conditions were as follows: solvent composition of 49.97%, extraction temperature of 35.7oC and extraction time of 50.71 min.Under these conditions,the experimental yield of gallic acid was 21.6253 ± 0.0528% mg gallic acid/100g bark,which was agreed close to the predicted value 21.6367 mg gallic acid/100g bark.The efficiency of the extraction techniques increased in the following order:shake flask extraction >Soxhlet > UAE > MAE.